Satisfaction levels of individuals who go to fitness centers - Uğurlu, Fatih Mehmet (Horizon Research Publishing, 2018)
The aim of this study is to determine the satisfaction levels of individuals who go to fitness centers. The model of the survey is a descriptive survey model. The sample of the study consists of 113 participants who were chosen by convenience sampling. The involvement of the participants into the study is based on the volunteerism principle. A survey form was used as the data-gathering tool in the study. The survey form consists of matters intended for personal information and the Sports Facilities Customer Satisfaction Scale. The data analysis in the study was conducted by using SPSS 21 package software. In the data analysis, descriptive statistics such as frequency, percentage, mean, standard deviation, minimum and maximum calculations were used. Additionally, in order to determine the relationship between the personal information and the sports facilities customer satisfaction, Mann Whitney U and Kruskal Wallis H tests were conducted. In the study, it was discovered that the participants determined the trainers’ attitude to be the most positive perception while the hygiene was the most negative perception. In the analysis of the customer satisfaction in terms of the personal information, it was determined that females’ trainer perception was lower compared to men and high school graduate individuals’ atmosphere perception was lower compared to the other individuals. © 2018 by authors, all rights reserved.
Keywords: Customer satisfaction; Fitness centers; Sports